The validity of Ochetophila Poepp. ex Endl. (Rhamnaceae: Colletieae) - Medan, Diego (2009)
It is shown that doubts raised recently (Feddes Rep. 119: 622–624, 2008) about the validity of Ochetophila Poepp. ex Endl. as distinct from Discaria Hook. are based on unsound arguments. The distinctness of Ochetophila rests upon a solid cladistic analysis of the tribe Colletieae (Rhamnaceae) and adequately reflects the current knowledge of this group. (© 2009 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)